Public policy and patterns of public governance - Zybała, Andrzej (Journal of Public Governance, 2014)
Formulating and implementing programmes and public policies is a very complex process, determined by many factors. The key factors are associated with the leading patterns of public governance. In Poland, they reflect a model that consists in governing by legislation and top-down control. They define to a great extent many key features of policy formulation and policy implementation, including the different types of relations between policy stakeholders (policy actors), and styles of policy execution (more hierarchical or partnership based). They also determine the extent to which policy knowledge is valued among policymakers and used in policymaking; and whether policies are formulated based on evidence or on the decision makers’ authoritarian approach. In reality, existing patterns and characteristics of publicgovernance in Poland do not contribute to a more effective process for formulating and executing policies.